Original Sin and Its Relation to Teaching Infant Baptism - Pane, Exson Eduaman (8ISC Proceedings: Theology; 8ISC Proceedings: Theology, 2022)
Adam’s transgression resulted in initial guilt and pollution that is called original sin. The teaching of original sin became prominent for some theologians in the fourth century and, at the same time, became one of the most controversial. However, it was accepted as a part of Christian doctrine for some Christian denominations. One of the prominent theologians who impressed so much with this teaching is Augustine of Hippo. Augustine’s notion of original sin arose from his dilemma and query about the influence of Adam’s sin on his posterity during the fifth century B.C. He thought that all people who participated in Adam’s first transgression and original sin were passed down to their children through their parents automatically without awareness of their children. The understanding of Augustine regarding original sin was not originated from his view on the Bible perspective but was influenced through his exploration of the view of Neo-Platonism on sin. According to Neo-Platonism, the nature of the soul and its relationship to the body as self-isolation is the root of sin. Before entering the body, the soul has a previous existence. The souls become wrapped in the body when they descend. But the point is that even before the soul enters the body, its illogical components have an unruly and terrible disposition. Augustine’s perspective on original sin influenced the church’s stance on infant baptism. The majority of Christian denominations accepted that every child inherited sin from their parents. The newborn baby must be baptized in order to be cleansed of the original sin. As a result, the purpose of this research is to examine the teaching of original sin and its relationship to the teaching of infants. Keywords: Original Sin, Infant Baptism, Transmission